Pengaruh Teknik Relaksasi Autogenik Terhadap Kualitas Tidur Pada Penderita Hipertensi Di Puskesmas Sumbang I - Dyah Palupi Puspita Dewi; Rakhmat Susilo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: This study aims to determine the effect of autogenic relaxation therapy on sleep quality in patients with hypertension. Methods: This research is a quantitative study with a pre-experimental one-group approach and pretest-posttest design. The sampling technique used was purposive sampling with a total of 28 respondents according to the inclusion and exclusion criteria. The research instrument employed the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Results: The results of this study show that the sleep quality of hypertension patients before autogenic relaxation therapy is at the level of poor sleep quality with an average score of 15.21. Meanwhile, after being given the intervention, the average score of sleep quality for hypertension sufferers decreases to 7.18 with the majority in the category of good sleep quality. In addition, Wilcoxon test results p-value = 0.000.Conclusion: This study concludes that there is an effect of autogenic relaxation therapy on the sleep quality of hypertension patients at Puskesmas I Sumbang. This study is expected to be used as a reference for pharmacological companion therapy for hypertension patients with sleep disorders.